2019
DOI: 10.1038/s41598-019-44226-y
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Tumor Burden and Loci as Predictors of First Line Sunitinib Treatment Efficacy in Patients with Renal Cell Carcinoma

Abstract: The aim of this study was to investigate the prognostic impact of baseline tumor burden and loci on the efficacy of first line renal cancer treatment with sunitinib. Baseline and on-treatment CT scans were evaluated. Both the Kaplan-Meier and Weibull modelling survival estimators have been used to describe sunitinib treatment response. Logistic regression was used to confirm associations between tumor site, burden and survival. Additionally, analysis of the metastases co-occurrence was conducted using the Baye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The total mass of tumor tissue, including the tumor cells distributed in bone marrow in patients with cancer, is referred to as a tumor burden [ 127 ]. Tumor burden surveillance is important in all phases of cancer management to prevent metastasis and recurrence [ 128 ].…”
Section: Further Use Of Ctdna In Nsclcmentioning
confidence: 99%
“…The total mass of tumor tissue, including the tumor cells distributed in bone marrow in patients with cancer, is referred to as a tumor burden [ 127 ]. Tumor burden surveillance is important in all phases of cancer management to prevent metastasis and recurrence [ 128 ].…”
Section: Further Use Of Ctdna In Nsclcmentioning
confidence: 99%
“…Estimating tumour burden and volume of disease in spinal metastases is difficult due to the shape of the vertebrae and presence of multiple vertebral levels. Tumour burden of spinal metastases has been shown to predict prognosis [ 106 , 127 , 128 , 129 ] and treatment efficiency [ 130 ]. With the help of AI, volumetric evaluation of spinal metastases and disease burden can be more efficient, clinically feasible and could aid clinical management.…”
Section: Discussionmentioning
confidence: 99%
“…A recent prospective study has shown that tumor burden and location of metastasis influence the rate of progression-free survival of patients with metastatic RCC using tyrosine kinase inhibitor (TKI), with pulmonary metastasis as the only positive predictor and skin as the worst predictor [5] , [6] . Although due to the limited investigation of skin metastasis, this case report shows regression of skin metastasis after the administration of pazopanib.…”
Section: Discussionmentioning
confidence: 99%